2014
DOI: 10.1007/s00107-014-0815-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the water uptake of wood veneers through plasma treatment at atmospheric pressure

Abstract: In order to provide a database which documents the influence of plasma treatment on water uptake of wood veneers, veneers of 27 wood species underwent immersion tests in untreated and plasma-treated states. Plasma treatment was executed using an air driven dielectric barrier discharge at atmospheric pressure. The results showed that plasma treatment led to significantly improved water uptake for most of the wood species, but some wood species remained unaffected after plasma treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…To overcome the threat of resistance development in lice, a physical treatment method was developed based on the concept of cold atmospheric pressure plasma (CAPP). As a key technology, CAPPs are currently used for purposes of surface modifications, like enhancement of wettability [6,7,8], precision cleaning purposes [9,10,11], or within the field of plasma medicine [12,13,14]. Known to be capable of interacting with biological surfaces and wounds, CAPPs have been developed to treat different diseases, ranging from skin diseases (e.g., [15,16,17,18]) to different cancer treatment approaches (e.g., [19,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the threat of resistance development in lice, a physical treatment method was developed based on the concept of cold atmospheric pressure plasma (CAPP). As a key technology, CAPPs are currently used for purposes of surface modifications, like enhancement of wettability [6,7,8], precision cleaning purposes [9,10,11], or within the field of plasma medicine [12,13,14]. Known to be capable of interacting with biological surfaces and wounds, CAPPs have been developed to treat different diseases, ranging from skin diseases (e.g., [15,16,17,18]) to different cancer treatment approaches (e.g., [19,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…As atmospheric‐pressure dielectric barrier discharges (AP‐DBDs) were further developed and studied, their applications were extended to multiple technological fields, including the functionalization of heat‐sensitive wood samples. For example, AP‐DBDs operated in N2, O2, and air were successfully used as an alternative way to sanding as well as for surface wettability modification leading to enhanced adhesion properties . Furthermore, incorporation of gaseous or liquid precursors in the plasma can lead to the deposition of thin layers protecting wood surfaces against water, fire, and molds …”
Section: Introductionmentioning
confidence: 99%
“…Plasma-based modification of wood surface using air as the process gas is known to improve wetting characteristics [13][14][15], which enhances the adhesion of coatings and adhesives [16][17][18][19]. Additionally, the uptake characteristics of wooden materials for water and waterbased modification agents are positively affected by plasma modification [20][21][22][23] as well as the penetration depth of adhesives applied to pre-treated wood surfaces [24]. Chen et al reported an increase in the adhesive strength of plywood made of plasma-treated poplar veneers [25].…”
Section: Introductionmentioning
confidence: 99%